Kepemimpinan Transformatif Perkembangan dan Implementasinya pada Lembaga Pendidikan - Indah Komsiyah (Ta'allum: Jurnal Pendidikan Islam, 2016)
Organizations must be seen as an open system today. With the open-ended nature of leaders and leadership is a strategic factor in an organization. The process of leadership in organizations occurs because of the element leader. Leaders are human individuals. Meanwhile, the leadership is inherent to him as a leader. In this case, there are many theories about leadership styles are offered, all have strengths and weaknesses. Theories that are considered effective or superior are the theory of transformational leadership. Namely, a leadership approach to doing business alters consciousness, to excite and inspire subordinates or members of the organization to expend extra effort in achieving organizational goals without feeling pressured or stressed. From the description, assessment of transformative leadership is necessary, including development of leadership transformative with the focus of discussion: 1) the origin of transformative leadership, 2) development of the concept of transformative leadership, 3) the development of the definition of transformative leadership, 4) development of the implementation of transformative leadership in educational institution.